Instantons in N=4 Sp(N) and SO(N) theories and the AdS / CFT correspondence - Timothy Hollowood (1999)
Following work on theories with SU(N) gauge groups, we perform a large-N saddle-point approximation of the measure for ADHM multi-instantons in N=4 supersymmetric gauge theories with symplectic or orthogonal gauge groups. For Sp(N) we find that a saddle-point only exists in the even instanton charge sector. For either Sp(N) or SO(N) the saddle-point solution parametrizes AdS_5 x RP^5, the dual supergravity geometry in the AdS/CFT correspondence for these theories. The instanton measure at large-N has the form of the partition function of ten-dimensional N=1 supersymmetric gauge theory with a unitary gauge group dimensionally reduced to zero